Exponentially asymptotic adaptive tracking control of nonstrict feedback nonlinear systems. Issue 2 (25th January 2022) - Liang, Yanjun; Li, Yuan-Xin; Che, Weiwei
Abstract : This paper considers the asymptotic adaptive tracking control issues for the nonstrict feedback nonlinear systems. By adding the negative exponential function to the Lyapunov function, the exponentially asymptotic convergence is realised for the first time. In addition, the prior knowledge of the lower and upper bounds of unknown nonlinear functions have been removed in this article. The unknown nonlinear functions and uncertain external disturbance are solved by using fuzzy logical systems (FLS) and the bound-estimation method. It is shown that the tracking error can converge to zero at an exponential rate and the whole signals of the controlled system are bounded. Finally, simulation examples have been presented to prove the effectiveness of the raised scheme.